Enhancing Educational Factors to Address Language Dilemmas In The ELT Class - Nurraida, Nurraida; Islami, Cut Muftahul; Daulay, Sholihatul Hamidah (Yayasan Insan Cipta Medan, 2024)
Language dilemmas, encompassing linguistic, cultural, and socio-economic factors, present substantial challenges within English Language Teaching (ELT) classrooms, affecting educators and learners alike. This article delves into the nuanced exploration and development of educational factors meticulously designed to tackle these multifaceted dilemmas head-on. A comprehensive examination elucidates how integrating innovative teaching strategies, cultivating a nurturing and inclusive learning atmosphere, and using technology empower educators to elevate language acquisition processes and dismantle barriers inhibiting effective communication within ELT environments. By synthesizing these pivotal elements, this study underscores the transformative potential of proactive pedagogical approaches in reshaping ELT landscapes and fostering enriched learning experiences for educators and learners.